An affinity triggered MRI nanoprobe for pH-dependent cell labeling. Issue 114 (2nd December 2016) - Palma, Susana I. C. J.; Fernandes, Alexandra R.; Roque, Ana C. A.
Abstract : The pH-sensitive affinity pair composed by neutravidin and iminobiotin was used to develop a multilayered Magnetic Resonance Imaging (MRI) nanoprobe responsive to the acidic pH of tumor microenvironment. Abstract : The pH-sensitive affinity pair composed by neutravidin and iminobiotin was used to develop a multilayered Magnetic Resonance Imaging (MRI) nanoprobe responsive to the acidic pH of tumor microenvironment. The multilayer system was assembled on meso -2, 3-dimercaptosuccinic acid-coated iron oxide magnetic nanoparticles (MNP), which convey negative MRI contrast enhancement properties to the nanoprobe. The outer stealth PEG-layer is altered in acidic media due to the disruption of interactions between neutravidin–iminobiotin. As a consequence, the positively charged inner layer is exposed and enhances interactions with cells. The nanoprobe uptake by HCT116 cells cultured in vitro under acidic conditions had a 2-fold increase compared to the uptake at physiological pH. The uptake difference is particularly clear in T 2 -weighted MRI phantoms of cells incubated with the nanoprobes at both pH conditions. This work sets the proof-of-concept of a MNP-based MRI nanoprobe targeting acidic tumor microenvironment through the use of a specific bio-recognition interaction that is pH-sensitive. This tumor targeting strategy is potentially applicable to the generality of tumors since the typical hypoxic conditions and high glycolysis rate in cancer cells create an acidic environment common to the majority of cancer types.